Workplace Pedagogic Practices: Understanding Learning Among Beginning Occupational Therapists - Toal-Sullivan, Darene (University of Ottawa (Canada), 2010)
It is a critical time in health care characterized by new models of service delivery, complexity of care, diverse practice environments, and evolving regulatory and legislative requirements. This is accompanied by recognition that the experiences and supports provided by workplaces are critical for initially developing the knowledge required for work and also for lifelong learning. In occupational therapy, there is relatively little understanding of how beginning occupational therapists learn to practice and how they resituate knowledge learned in the context of school, to the context of work. The objective of this research was to understand how beginning occupational therapy practitioners learn in the practice context, how clients mediate practitioners' learning, and the factors which shape practitioners' participation and learning through work. This qualitative study used an ethnographic approach to understand the situated practices, interactions and actions of occupational therapists in an acute care hospital context. Data collection consisted of semi-structured interviews, observations of practice, participant journal entries, researcher journal entries and meetings with the occupational therapy manager, over a period of twelve months. The study participants comprised five occupational therapists with less than two years of clinical experience. Activity theory provided an integrative, conceptual framework to understand how knowledge is co-constructed and distributed across a particular hospital system. The findings of this research help us understand how workplace affordances and constraints, and individuals' agency shape beginning occupational therapists' participation and learning through work. There are complex relations and interactions among the components of the activity system engaged in the object of patient care. A conceptual framework, the Workplace Learning Model for Occupational Therapy, was developed to understand how learning occurs in practice and the pedagogic means to support occupational therapists' engagement in work. The findings of this study contribute to the evidence in workplace learning and participation.
Keywords: Health Sciences, Occupational Therapy.; Education, Health.